Pengembangan Pembelajaran Kelas Melalui Metode Inquiry Discovery dan Pendekatan Motivasi Pendidik Bidang Ilmu Geologi - Prayitno, Budi; Kasarian, Husnul; Heriyanto (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2024)
The inquiry discovery method was tested on 18 students/I level XII IPA consisting of 11 boys and 7 girls through 2 face-to-face trials. From the results of the evaluation experiment, there is a range of values between 55 – 60 which is 44.44% while the range of values 60.01 – 70.00 is 55.55% (before implementation). Furthermore, the percentage of learning achievement from the 70-80 score range is 72.22% and the 80-90.00 range is 27.77% (after implementation). While the results of the evaluation analysis using the Liliofers Test were found to be not normally distributed, while the analysis using the Wilcoxon Match Pairs Test found that there were significant differences in the results of the evaluation before and after treatment. From the results of these tests, it can be concluded that repetition of the inquiry discovery method can increase scientific thinking independently so that achievement and completeness during the educational process can be directed according to the learning implementation plan for SMA CENDANA PEKANBARU.